Effect Of Discipline And Motivation On The Performance Of Catholic Religious Education Teachers At The Office Of The Ministry Of Religion, Tana Toraja District - Chornelius Ranteallo; Muspa; Suwandaru, Rachman; Syam, Faisal (MANAGER: Journal of Management and Administration Science, 2023)
The formulation of the problem in this study is whether there is an effect of discipline and motivation on the performance of Catholic religion teachers at the office of the Ministry of Religion in Tana Toraja Regency. The purpose of the study was to determine the effect of discipline and motivation on the performance of Catholic religion teachers at the ministry of religion office in Tana Toraja district. This research is an associative type of research, and the location of this research is Jln. Pongtiku No.106, Pantan, District, North Makale, Tana Toraja Regency, South Sulawesi. The sample in this study was 32 people, with saturated sampling techniques. The data used are primary and secondary data. Data collection methods include questionnaires and documentation. The data analysis used is quantitative. The analysis technique uses multiple linear regression through the SPSS Version 29 application: f test (simultaneous), t test (partial). The test results that have been carried out from this study show that the results of multiple linear regression calculations obtained Y = 6.101 + 0.661 X1 + 0.772 X2. For the t test of the discipline variable (X1), t count (2.89)> t table (2.05), meaning that discipline partially affects performance. The t test of the motivation variable (X2) obtained a t count (2.57) > t table (2.05), meaning that motivation partially affects performance. for the f test, f count (10.78) > f table (3.33), meaning that there is a significant effect of discipline and motivation (simultaneously) on the performance of Catholic religion teachers at the office of the ministry of religion of the Tana Toraja district.